Faculty fathers: Understanding the experiences of faculty men with children during the COVID‐19 pandemic. Issue 199 (25th October 2022) - Blakewood Pascale, Amanda; Ehrlich, Suzanne; Hicks‐Roof, Kristen
Abstract: To effectively cultivate systems of equity, it is important to not only understand the experiences of those who are most affected by inequity but also of those who are in positions of power and privilege. This study explores how faculty men with children navigated the pandemic experience. Two major thematic findings emerged including 'Not (as) Interrupted' and '"I" feel supported'. These findings suggest that academic fathers may be emerging from the pandemic positioned differently than academic mothers. This research has implications for higher education administrators and faculty in the shaping of practice and policies aimed at equitably supporting faculty post‐pandemic.